Audit Fees, Audit Tenure, Auditor Industry Specialization, Audit Firm Size, and Audit Quality: Evidence from Indonesian Listed Companies - Ananda, Citra; Faisal, Faisal (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study aims to examine determinants of audit quality in companies listed on the Indonesia Stock Exchange (IDX). The audit quality determinants tested in this study are audit fees, audit tenure, auditor industry specialization and audit firm size. Using purposive sampling method, a total of 240 companies listed on IDX between 2018 and 2020 (720 observations) were selected as the research samples. The panel regression analysis with a random effect model was applied to test the hypotheses. The results of this study show that audit fees and auditor industry specialization have a negative effect on audit quality proxied by discretionary accruals, while audit tenure and audit firm size have a positive influence on audit quality. These results indicate that audit tenure and audit firm size are crucial factors for maintaining audit quality.